Pengaruh Pendidikan Kesehatan Tentang Pernikahan Dini terhadap Tingkat Pengetahuan dan Sikap Remaja di Puskesmas Tinggi Raja Kecamatan Tinggi Raja Kabupaten Tinggi Raja Tahun 2023 - Endang Apriyanti; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Rahmah Rahmah (Journal of Educational Innovation and Public Health, 2025)
Adolescence is marked by growth and development in various aspects, including physical, psychological, and intellectual. They tend to have a great sense of curiosity, like challenges, and dare to take risks. However, this also makes them vulnerable to various risks, both in the short and long term. Therefore, health services are needed that care about the needs of adolescents, especially in terms of reproductive health. This study aims to determine whether there is an Influence of Health Education About "the influence of health education about early marriage on the level of Knowledge and attitudes of adolescents at the Tinggi Raja Health Center. Tinggi Raja Village, Tinggi Raja District in 2023. The type of quasi-experimental research with a One Group Pretest-Posttest Design, the research sample amounted to 30 people, who were selected using a sampling technique with the Total Sampling Technique. Based on the results of statistical tests using the Wilcoxon test, the results of the p value of knowledge = 0.000 <0.05 and the p value of attitude = 0.000 <0.05. So it is proven that there is a significant influence between health education about early marriage on the level of knowledge and attitudes of adolescents at the Tinggi Raja Health Center. Tinggi Raja Village, Tinggi Raja District in 2023.